2002
DOI: 10.1086/345771
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Human Immunodeficiency Virus Type 1 RNA Associated with Herpes Simplex Virus Reactivation and Suppression

Abstract: In early trials of antiretroviral therapy, acyclovir was associated with increased survival by an unknown mechanism. The hypothesis that subclinical herpes simplex virus (HSV) reactivation was associated, in vivo, with increased plasma human immunodeficiency virus (HIV) RNA and suppression with a reduced plasma HIV RNA load was investigated. HSV cultures were performed daily on HSV-2-positive/HIV-positive patients, and plasma HIV-1 RNA loads were measured at regular intervals. A subset of patients prior to, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
136
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 42 publications
5
136
1
Order By: Relevance
“…by guest www.bloodjournal.org From shown to coexist in the same recurrent herpetic lesion. 44 Thus, coinfection or adjacent infection of epidermal and perhaps dermal DCs in these lesions with these viruses is probable. In these studies highly purified viral preparations and similar multiplicities of each virus were used over a range of 1-10 per cell.…”
Section: Discussionmentioning
confidence: 98%
“…by guest www.bloodjournal.org From shown to coexist in the same recurrent herpetic lesion. 44 Thus, coinfection or adjacent infection of epidermal and perhaps dermal DCs in these lesions with these viruses is probable. In these studies highly purified viral preparations and similar multiplicities of each virus were used over a range of 1-10 per cell.…”
Section: Discussionmentioning
confidence: 98%
“…Doubts about this HSV-2-HIV-1 relationship, engendered by failure of antiviral suppression of recurrent genital herpes to affect HIV-1 acquisition, are now being understood in terms of the failure of antivirals to completely suppress HSV-2 shedding and epithelial microulcers (7)(8)(9). Conversely HIV-1 + , HSV-2 + individuals also shed HIV-1 more frequently than those without HSV-2, because of increased viral shedding through genital ulcers (10).…”
mentioning
confidence: 99%
“…There is evidence of more rapid HIV-1 disease progression in dually infected individuals (6,15,29) as well as in vitro data demonstrating that HSV-2 proteins can activate the HIV-1 long terminal repeat, leading to increased HIV-1 replication (10,18,23). Recent trials of acyclovir monotherapy for HSV-2 infection in HSV-2/HIV-1-coinfected individuals showed an approximately 0.33 to 0.5 log 10 decrease in HIV-1 plasma levels, but the overall benefits of this approach remain unclear (24,30,36). One study reported that acyclovir therapy in HSV-2/HIV-1-coinfected patients did not prevent transmission of HIV-1 to uninfected partners (4).…”
mentioning
confidence: 99%